Individual and contextual antecedents of workplace aggression in aged care nurses and certified nursing assistants. Issue 4 (August 2015) - Rodwell, John; Demir, Defne; Gulyas, Andre
<x xml:space="preserve">Abstract</x> Employees in aged care are at high risk of workplace aggression. Research rarely examines the individual and contextual antecedents of aggression for specific types of workers within these settings, such as nurses and certified nursing assistants (CNAs). The study aimed to explore characteristics of the job demands‐resources model (JD‐R), negative affectivity (NA) and demographics related to workplace aggression for aged care workers. The survey study was based on 208 nurses and 83 CNAs working within aged care. Data from each group were analysed separately using ordinal regressions. Both aged care nurses and CNAs reported high rates of bullying, external emotional abuse, threat of assault and physical assault. Elements of the JD‐R model and individual characteristics were related to aggression types for both groups. Characteristics of the JD‐R model, NA and demographics are important in understanding the antecedents of aggression observed among aged care workers.